2018
DOI: 10.1007/s11104-018-3866-4
|View full text |Cite
|
Sign up to set email alerts
|

Soil sterilization, pathogen and antagonist concentration affect biological control of Fusarium wilt of cape gooseberry by Bacillus velezensis Bs006

Abstract: Background and aim Fusarium wilt (FW) is the major constraint on cape gooseberry (Physalis peruviana L.) production. Fungicides have been ineffective in disease control and alternative tools are not available. Bacillus velezensis (formerly Bacillus amyloliquefaciens) strain Bs006 has an antagonistic potential against Fusarium oxysporum f. sp. physali (Foph). However, results of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 50 publications
5
30
0
Order By: Relevance
“…Foph management practices in cape gooseberry crops have been mainly based on the use of synthetic fungicides (Moreno-Velandia et al, 2019); however, synthetic elicitors have been used as alternatives for soilborne pathogen management in recent years (McGovern, 2015). Studies about synthetic elicitors have been focused separately on disease control (Ding et al, 2009a;Mandal et al, 2009;Mostafa et al, 2018) or their effect on abiotic stress mitigation (Csisz ar et al, 2018;Mansori et al, 2015;Rao and Dixon, 2017); however, the available literature on the use of these compounds to reduce the negative impact generated by combined stresses (pathogens and abiotic stresses) in Andean fruit trees, such as cape gooseberry, is still scarce.…”
mentioning
confidence: 99%
“…Foph management practices in cape gooseberry crops have been mainly based on the use of synthetic fungicides (Moreno-Velandia et al, 2019); however, synthetic elicitors have been used as alternatives for soilborne pathogen management in recent years (McGovern, 2015). Studies about synthetic elicitors have been focused separately on disease control (Ding et al, 2009a;Mandal et al, 2009;Mostafa et al, 2018) or their effect on abiotic stress mitigation (Csisz ar et al, 2018;Mansori et al, 2015;Rao and Dixon, 2017); however, the available literature on the use of these compounds to reduce the negative impact generated by combined stresses (pathogens and abiotic stresses) in Andean fruit trees, such as cape gooseberry, is still scarce.…”
mentioning
confidence: 99%
“…However, the objective of this study was to evaluate options with a practical application from the agronomic and physiological points of view. Studies to find complementary alternatives to manage vascular wilt caused by Foph in Andean fruit crops have been limited to the use of fungicides and have been recently focused on biological control agents [7,8]. Therefore, our research demonstrated the potential use of BR, SA or BE for Foph control in cape gooseberry.…”
Section: Discussionmentioning
confidence: 82%
“…Young mycelium segments from the supplied strain were cultured in 50 mL of Potato Dextrose Broth (PDB; Difco TM , Becton Dickinson, Sparks, MD, USA) in 250 mL Erlenmeyer flasks. Then, segments were incubated for 7 days under constant agitation in an orbital shaker (Lab-Line, Melrose Park, IL, USA) at 125 rpm and 28 • C under dark conditions [8].…”
Section: Plant Inoculation and Resistance Elicitors Applicationmentioning
confidence: 99%
“…In addition, there is an increasing demand by consumers for food free of agrochemical residues and production processes that are friendlier to the environment. Because of these issues, alternatives to the use of agrochemicals, such as biological control and the application of organic additives, have gained interest recently (Moreno-Velandia et al, 2018;Pal and Gardener, 2006).…”
mentioning
confidence: 99%
“…The search for management alternatives based on biological control, particularly the application of biocontrol agents and their effect on the disease, has become very important in the cape gooseberry-F. oxysporum pathosystem in Colombia (Díaz et al, 2013;Moreno-Velandia et al, 2018). However, information on the use of products of natural origin, such as chitosan and burned rice husk, on vascular wilt and the physiological response of cape gooseberry plants is still scarce.…”
mentioning
confidence: 99%